Comparison of Maternal Serum Levels and Placental mRNA Levels of Dickkopf-1 in Preeclamptic and Normal Pregnant Women at Delivery - Kasoha, Mariz; Takacs, Zoltan; Fackiner, Lena; Gerlinger, Christoph; Sklavounos, Panagiotis; Radosa, Julia; Solomayer, Erich-Franz; Hamza, Amr (Geburtshilfe und Frauenheilkunde, 2021)
Background Preeclampsia remains a major cause of perinatal and maternal mortality and morbidity worldwide. Wnt/β-catenin signaling is known to be critically involved in placenta development processes. Dickkopf-1 (DKK1) is a key regulator of this transduction pathway. The aim of this study is to compare maternal serum DKK1 levels and placental mRNA levels of DKK1 and β-catenin in preeclamptic and normal pregnant women at delivery.Methods The present study included 30 women with preeclampsia and 30 women with normal pregnancy. Maternal serum DKK1 levels were measured by ELISA. Placental mRNA levels of DKK1 and β-catenin were detected using RT-PCR.Results Decreased maternal serum DKK1 levels were associated with worse maternal and fetal complications including HELLP syndrome, determination of one or more pathological symptom and IUGR diagnosis. No significant difference in maternal serum DKK1 levels was reported between preeclamptic women and women with normal pregnancy. Placental mRNA DKK1 levels were lower in preeclamptic women compared with normal pregnant women. Placental mRNA β-catenin levels showed no significant difference between two groups.Conclusions Our findings reported the aberrant placental mRNA DKK1 levels in patients with preeclampsia. In addition, worse preeclampsia features were associated with decreased maternal serum DKK1 levels. Hence, aberrant Wnt/β-catenin signaling might present a plausible mechanism in preeclampsia pathogenicity. Dysregulated expression of DKK1 at gene level in the placenta but not at protein level in the maternal serum might confirm the notion that preeclampsia is a type of placenta-derived disease.
Keywords: preeclampsia; Wnt/β-catenin signaling; Dickkopf-1 (DKK1); serum; placenta; pathogenicity